Shipworm symbiosis ecology-guided discovery of an antibiotic that kills colistin-resistant Acinetobacter. Issue 11 (18th November 2021) - Miller, Bailey W.; Lim, Albebson L.; Lin, Zhenjian; Bailey, Jeannie; Aoyagi, Kari L.; Fisher, Mark A.; Barrows, Louis R.; Manoil, Colin; Schmidt, Eric W.; Haygood, Margo G.
Summary: Teredinibacter turnerae is an intracellular bacterial symbiont in the gills of wood-eating shipworms, where it is proposed to use antibiotics to defend itself and its animal host. Several biosynthetic gene clusters are conserved in T. turnerae and their host shipworms around the world, implying that they encode defensive compounds. Here, we describe turnercyclamycins, lipopeptide antibiotics encoded in the genomes of all sequenced T. turnerae strains. Turnercyclamycins are bactericidal against challenging Gram-negative pathogens, including colistin-resistant Acinetobacter baumannii . Phenotypic screening identified the outer membrane as the likely target. Turnercyclamycins and colistin operate by similar cellular, although not necessarily molecular, mechanisms, but turnercyclamycins kill colistin-resistant A. baumannii, potentially filling an urgent clinical need. Thus, by exploring environments that select for the properties we require, we harvested the fruits of evolution to discover compounds with potential to target unmet health needs. Investigating the symbionts of shipworms is a powerful example of this principle. Graphical abstract: Highlights: Microbial competition in a symbiosis leading to antibiotics Group of lipopeptide antibiotics that targets drug-resistant Acinetobacter Abstract : The symbiotic bacteria associated with marine shipworms are prolific producers of bioactive metabolites. Miller et al. use an ecology-guided approach to isolate the turnercyclamycins, proposed to be important for this association. Turnercyclamycins are described as a group of lipopeptide antibiotics with selective activity against Gram-negative pathogens, including drug-resistant Acinetobacter .